An in vitro study into the effect of zinc substituted hydroxyapatite on osteoclast number and activity. Issue 11 (29th January 2014) - Shepherd, David V.; Kauppinen, Kyösti; Brooks, Roger A.; Best, Serena M.
Abstract Zinc ions have been shown to inhibit osteoclast development and proliferation both in vitro and in vivo. The same inhibiting effect has been observed in vitro when zinc was substituted into tri‐calcium phosphate (TCP). Because of the solubility of TCP it is not an ideal candidate for a material to inhibit osteoclast activity in the long term. Hydroxyapatite (HA) is less soluble and so potentially offers a more long‐term, sustainable effect. Previous work has shown that zinc can successfully be substituted into HA and still retain phase purity after heat treatment. The study reported here presents the effects of zinc substituted HA on the development and activity of osteoclast‐like cells. It was found that increasing zinc substitution levels led to a decrease in the number of these cells present after 21 days. When resorption activity was investigated it was found that an increase in the amount of zinc present in the discs led to a significant decrease in the amount of resorption taking place on the discs. These results provide evidence for the potential of zinc substituted HA as a material to reduce resorptive activity to provide long‐term bonding of implant to bone. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 4136–4141, 2014.